Kajian Daerah Resapan Air Sebagai Peningkatan Sumber Daya Air Desa Krambilsawit Kecamatan Saptosari Kabupaten Gunungkidul - Kristiawan, Yanuarius Benny (Jurnal Atma Inovasia, 2021)
Krambil Sawit Village often experiences drought and sometimes it is difficult to get clean water sources. Biopores, absorption wells and reforestation are methods to maintain water availability by conserving groundwater. The purpose of this research is to provide important knowledge and information to residents in Krambil Sawit village, Gunung Kidul, Yogyakarta to obtain clean water by making biopores, absorption wells and reforestation. In this Kuliah Kerja Nyata (KKN) using online system, the method used is a qualitative research method that begins with conducting a location survey and analyzing data from Krambil Sawit Village, google maps, and online news portals available on Google. Socialization of biopores, absorption wells, and reforestation through videos and e-books  made by groups 35 KKN  78. The results of the community service research conducted by the 35 Group were that the community obtained important knowledge and information regarding groundwater conservation by making biopic infiltration holes, infiltration wells and improved reforestation that can process standing rainwater into a source of clean water that is beneficial to residents around the village. Krambil Sawit Village, Gunung Kidul, Yogyakarta